The Use of Artificial Intelligence in Analyzing the Grounds for Annulment of Arbitral Awards in Financial Disputes - Dawoud, Belal; Alayasa, Jamal; Al Ahmad, Sohail; Saabneh, Mohammad (Ahliya Journal of Business Technology and MEAN Economies, 2026)
This study aimed to examine the extent to which artificial intelligence technologies can be relied upon to analyze the grounds for the invalidity of arbitration awards issued in financial disputes, and to identify the procedural and substantive defects that may affect the validity of these awards. The study adopted the analytical, comparative, and foundational jurisprudential methodologies. It concluded that artificial intelligence technologies possess an exceptional capacity to analyze complex legal data and detect indicators of invalidity related to the validity of the arbitration agreement, the arbitral tribunal exceeding its jurisdiction, violations of the right to defense, and contraventions of public order. However, its role remains strictly limited to technical and analytical support and cannot replace human discretionary authority and oversight. Furthermore, its utilization aligns with the objectives of Sharia provided it adheres to transparency and the prevention of algorithmic injustice. Accordingly, the study recommended urgent legislative intervention to amend the Palestinian Arbitration Law No. (3) of 2000 by incorporating provisions that permit the use of artificial intelligence in managing procedures and analyzing documents, while explicitly stipulating that its outputs shall not be inherently binding, subjecting them to human oversight, and providing strict guarantees to protect the confidentiality of data and financial information. The scientific originality of this study lies in addressing a novel legal and technical issue that has not been comprehensively examined in previous literature. It integrates the analysis of the grounds for invalidating arbitration awards in financial disputes with the employment of artificial intelligence technologies to identify such grounds, and compares the stances of Palestinian law and Islamic jurisprudence regarding this technology. This approach fills a legislative and jurisprudential gap and establishes a comprehensive framework for the controls governing digital justice in arbitration.